The Effect Of The Cash Transfer For Poor Students Program On Student Education Expenditures: Evidence From Indonesia - Ramiayu, Deasy Dwi; Handayani, Dwini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The Cash Transfers for Poor Students Program (Bantuan Siswa Miskin, BSM)―formerly known as Program Indonesia Pintar―aims to improve financial capacity for poor and vulnerable students. However, there is limited research that measures the effect of the BSM program on student education expenditure by school level in Indonesia. Using pooled cross-section data from the Indonesia Family Life Survey (IFLS), this study examines the effect of the BSM program at three levels of education namely primary, junior secondary, and senior secondary. By conducting the Propensity Score Matching (PSM) and pooled cross-section regression, this study finds that the BSM program has a significant and positive effect by 8.5 percent on student education expenditure at senior secondary level, in contrast, no effect on primary and junior secondary school students. This study suggests that the government needs to adjust the value of program benefits as the burden of student education expenditure continues to be high.